Integrated Material Center Business Model for Improving Financial Performance and Supply Chain Efficiency of Metal SMEs - Oviyan Patra; Judi Harsono (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Small and Medium Enterprises (SMEs) in the metal industry in Mekarmaju Village, Bandung Regency, have great potential to support the local economy and the manufacturing industry supply chain. However, in practice, metal SMEs still face various structural problems. This study aims to examine financial performance due to the development of a business and operational model for a material center for SMEs in the metal industry. This study uses a qualitative descriptive approach. The data collection techniques used in this study are literature review, field observation, and focus group discussion. The data obtained was analyzed using qualitative descriptive analysis through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the establishment of a material center with an integrated business model is an effective strategy to strengthen and develop metal SMEs. Through improvements in the supply chain, raw material management, logistics, warehousing, and the implementation of coordinated quality control, this model increases the efficiency, consistency of quality, and competitiveness of SME products. Its success is highly dependent on operational readiness, commitment to cooperation among stakeholders, and continuous assistance from the government, especially the role of the Ministry of Industry.